2021
DOI: 10.1016/j.cyto.2021.155491
|View full text |Cite
|
Sign up to set email alerts
|

Functional genetic variants of the IFN-λ3 (IL28B) gene and transcription factor interactions on its promoter

Abstract: Interferon lambda 3 (IFN-λ3 or IFNL3, formerly IL28B), a type III interferon, modulates immune responses during infection/inflammation. Several human studies have reported an association of single nucleotide polymorphisms (SNP) in the IFNL3 locus with expression level of IFNL3. Previous genetic studies, in the context of hepatitis C virus infections, had predicted three regulatory SNPs: rs4803219, rs28416813 and rs4803217 that could have functional/causal roles. Subsequent studies confirmed this prediction for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Many studies have identified IFNL3 polymorphisms to be correlated with the outcome of hepatitis-C infection. Scholars have found that major alleles and favorable genotypes lead to higher expression of IFNL3 , better response to therapy, and viral clearance in patients ( 36 42 ). Unlike other research limited to infectious diseases, we investigated people with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified IFNL3 polymorphisms to be correlated with the outcome of hepatitis-C infection. Scholars have found that major alleles and favorable genotypes lead to higher expression of IFNL3 , better response to therapy, and viral clearance in patients ( 36 42 ). Unlike other research limited to infectious diseases, we investigated people with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has supplemented the member composition of type III IFN family, which is known as IFN-lambda 4. However, at present, there is more inclination to research about the functions related to IFN-Lambda 3 [14] . Previous studies have shown that IFN-alpha and sorafenib have antitumor effects on HCC in vitro and in vivo [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The IFNL locus has been under strong selective pressure during human evolution (Manry et al, 2011). Genetic variants have been identified that control the expression of IFN‐λ3 (rs28416813 and rs4803217) (Chinnaswamy et al, 2013; McFarland et al, 2014; Roy et al, 2021) and expression and activity of IFN‐λ4 (rs368234815 and rs117648444, respectively) (Prokunina‐Olsson et al, 2013; Terczyńska‐Dyla et al, 2014) (Figure 1a). These variants have been associated with several infectious and inflammatory diseases, including COVID‐19 (Chinnaswamy, 2016; Matic et al, 2023; Prokunina‐Olsson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The SNP (single nucleotide polymorphism) rs117648444 (G/A) is a non‐synonymous variant that changes the amino acid at 70th position in IFN‐λ4 from proline to serine (P70 or S70); the S70 variant has significantly reduced activity in terms of levels of IFN‐stimulated gene (ISG) expression compared to P70 in vitro and it phenocopies the TT allele that abolishes the expression of an active IFN‐λ4 due to disruption of the ORF, in association with tests involving HCV treatment response cohorts (Bhushan et al, 2017; Terczyńska‐Dyla et al, 2014). The SNPs rs28416813 (C/G) and rs4803217 (C/A) present in the 5′UTR and 3′UTR, respectively, of the IFNL3 gene potentially regulate the expression levels of IFN‐λ3 (Chinnaswamy et al, 2013; McFarland et al, 2014; Roy et al, 2021). The SNP rs12979860 (C/T) was the strongest signal in the HCV GWAS and is usually included as a proxy SNP for IFNL gene functional variants (Ge et al, 2009; Prokunina‐Olsson, 2019).…”
Section: Introductionmentioning
confidence: 99%